2020
DOI: 10.1108/bl-12-2019-0130
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-based society and emerging disciplines: a correlation of academic performance

Abstract: Purpose Digital libraries promote and accelerate scientific research in academic institutions. The subscribed database resources of digital libraries have become an increasingly valuable asset for researchers. Database resources help generate new ideas, determine research directions and promote productive academic interaction between teachers and students in the information age. The purpose of this study is to examine the use of electronic resources by students in various databases, the research productivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…54 A list of the bibliographic databases should be provided on the library website with instructions for their usage and relevant content should be made accessible discipline-wise through proper authentication login. 55 Services like "ask a librarian," search, searching via barcode scanners, and maintaining a rich database should be considered by each library through their online and mobile phone interfaces. 56 In developing smartphone-based library applications, it is essential to consider service quality, affinity, usefulness, ease of use, satisfaction, confirmation, and continuous usage.…”
Section: Resource Description Discovery and Accessmentioning
confidence: 99%
“…54 A list of the bibliographic databases should be provided on the library website with instructions for their usage and relevant content should be made accessible discipline-wise through proper authentication login. 55 Services like "ask a librarian," search, searching via barcode scanners, and maintaining a rich database should be considered by each library through their online and mobile phone interfaces. 56 In developing smartphone-based library applications, it is essential to consider service quality, affinity, usefulness, ease of use, satisfaction, confirmation, and continuous usage.…”
Section: Resource Description Discovery and Accessmentioning
confidence: 99%
“…While analyzing this in Pakistani scenario, Khuram et al (2017) have reviewed the current HEC's policies and their impact on motivation of faculty members and concluded that the existing HEC's faculty appointment criteria has increased the motivation amongst the faculty members to perform better. The performance measurement mechanism in current criteria is based solely on the research outcomes that is also only on the number of research publications (Rafi, Ahmad, Naeem, Khan, & JianMing, 2020). Hence, this study did not include any other factor to be associated with performance of faculty members.…”
Section: 1mentioning
confidence: 99%
“…This is also valid for the educational sector where the success of educational institutions typically hinges on teaching quality, i.e. faculty performance and organizational management practices (Rafi et al, 2020). In this context, academic managerialism nowadays has infiltrated university management, encouraging them to embrace management techniques that accentuate employee productivity (Niyazova, 2021).…”
Section: Introductionmentioning
confidence: 99%